Analysis of economic potential and feasibility of vaname shrimp cultivation business in Seuwwa Village, Pakue District, North Kolaka - Syamsuri Syamsuri; Naima Haruna; Hasria Alang (Arwana: Jurnal Ilmiah Program Studi Perairan, 2023)
The aim of the research is to analyze the economic potential and feasibility of the Vaname Shrimp cultivation business in that location. The method used is qualitative and quantitative. Qualitative is to see an overview of shrimp farming in the village, while quantitative analysis is to calculate the economic potential and business feasibility of Vaname Shrimp cultivation. This research was conducted in August-October 2022 in Seuwwa Village, Pakue District, North Kolaka Regency, Southeast Sulawesi Province. The location selection was done deliberately, data collection through observation and questionnaire assistance. Data analysis techniques to calculate economic potential through acceptance and income analysis, while data analysis techniques to determine business feasibility are using operating profit (OP), benefit cost ratio (BCR), payback period (PP), profit rate (PR), breakeven formulas. points (BEP), return on investment (ROI). The results showed that the Vaname Shrimp cultivation business in the research location obtained a profit or income of Rp. 17,073,000, OP value obtained 17,193,000, BCR 5.09, PP 0.24, PR 409.29%, production BEP 78.54 Kg, BEP value Rp. 7,854, and ROI 236.76%. Based on this, the Vaname Shrimp farming business in Seuwwa Village has economic potential and is feasible to continue.